Efektivitas Penggunaan Kahoot dalam Pembelajaran Pendidikan Pancasila untuk Meningkatkan Prestasi Belajar Siswa SMA - Berliana Sinurat (CIVICS: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2025)
This study is a classroom action research (CAR) that aims to improve student learning achievement in Pancasila Education subjects through the application of interactive Kahoot learning media. The subjects in this study were 36 students of grade XI - I at SMA Negeri 1 Rantau Utara. The study was conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The instruments used included teacher and student activity observation sheets, learning outcome tests, and documentation. The results showed that the use of Kahoot media can increase student interest and participation in learning, which has a positive impact on improving learning outcomes. The average student score increased from 68.5 in the pre-cycle to 76.2 in cycle I, and reached 83.4 in cycle II. Thus, the application of Kahoot media has proven effective in improving student learning outcomes in Pancasila Education subjects.